2021
DOI: 10.1158/1078-0432.ccr-19-4191
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the IFN Signaling Pathway is Associated with Resistance to CDK4/6 Inhibitors and Immune Checkpoint Activation in ER-Positive Breast Cancer

Abstract: Purpose: Cyclin-dependent kinase 4 (CDK4) and CDK6 inhibitors (CDK4/6i) are highly effective against estrogen receptor–positive (ER+)/HER2− breast cancer; however, intrinsic and acquired resistance is common. Elucidating the molecular features of sensitivity and resistance to CDK4/6i may lead to identification of predictive biomarkers and novel therapeutic targets, paving the way toward improving patient outcomes. Experimental Design: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 46 publications
4
60
0
Order By: Relevance
“…These rewired genes ( Figure 2 and Table 1 ) included genes associated with interferon alpha and gamma response, epithelial mesenchymal transition (EMT), the p53 pathway, and TNFα signaling via NFκB. Of note, the upregulation of interferon alpha and gamma signaling we observed in ER-positive NB73-resistant cells is also reported to be observed in endocrine-resistant ER-positive breast cancers [ 12 ].…”
Section: Resultsmentioning
confidence: 85%
“…These rewired genes ( Figure 2 and Table 1 ) included genes associated with interferon alpha and gamma response, epithelial mesenchymal transition (EMT), the p53 pathway, and TNFα signaling via NFκB. Of note, the upregulation of interferon alpha and gamma signaling we observed in ER-positive NB73-resistant cells is also reported to be observed in endocrine-resistant ER-positive breast cancers [ 12 ].…”
Section: Resultsmentioning
confidence: 85%
“…Interestingly, most LumA and LumB lncRNAs were related positively or negatively to the Interferon Gamma Response module. Recently, a study demonstrated that the activation of the interferon signaling pathway in ER+ BRCA relates to resistance to CDK4/6 inhibitors and immune checkpoint activation (40). Understanding the role of lncRNAs in this context may be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the FAT Atypical Cadherin 1 (FAT1) gene has also been identified at a small percentage of clinical samples (17), leading to dysregulation of the HIPPO pathway through the accumulation of key HIPPO pathway components and increased expression of CDK6. Other proposed mechanisms of CDK4/6i resistance include 1) upregulation of cyclin D isoforms (18)(19)(20), which may underlie the relative ineffectiveness of palbociclib and ribociclib as a single agent in the absence of an endocrine therapy backbone as ERa is still free to promote expression of cyclin D; 2) dysregulated early phosphorylation of pRb by CDK2 (21,22); 3) upregulation of proliferative signalling leading to pRb hyperphosphorylation via dysregulation of the phosphatidylinositol 3 kinase (PI3K) and mitogen activated protein kinase (MAPK) pathways, for example via upregulation of FGFR signalling (19,20,23,24); and 4) deregulation of immune associated pathways, for example increased interferon a and interferon g signalling that has been linked to reduced sensitivity and resistance and to CDK4/6i in clinical samples and preclinical models (25)(26)(27).…”
Section: Resistance To Cdk4/6i In Er+ Breast Cancermentioning
confidence: 99%